European Fiscal Harmonization and the French Economy - Perraudin, W. (IMF Working Papers; Working Paper ;, 1990)
This paper examines the implications of European fiscal harmonization for the French economy using a general equilibrium model. The latter extends the overlapping generations simulation model of Auerbach and Kotlikoff in three ways. A well-developed external sector is included. Households face constraints in their borrowing. The population comprises 'rich' and 'poor' households with different labor productivities. The harmonization policy that involves cuts in VAT and savings taxes leads to welfare losses for both rich and poor approximately equivalent to one percent of GDP.